Traumatic Brain Injury in Honduras: The Use of a Paper‑based Surveillance System to Characterize Injuries Patterns - Erica Johnson; Cristina Rodriguez; Juan C. Puyana; Francisco J. Bonilla-Escobar (University Library System, University of Pittsburgh, 2022)
Background: Traumatic brain injuries (TBI) are a leading cause of death and disability worldwide. Violence is the leading cause of mortality in Honduras. However, the incidence and impact of TBI in this low-middle income country (LMIC) is unknown. The aim of this study is to describe the epidemiology of TBI in Honduras, as captured by an injury surveillance tool in the country's major referral center. Methods: We conducted a cross‑sectional review of all TBI‑related emergency department visits at the main referral hospital in Honduras from January to December 2013. We calculated descriptive statistics from Injury Surveillance System (InSS) data. Results: Of 17,971 total injuries seen in 2013, 20% were traumatic brain injuries (n=3,588). The main mechanisms of injury were falls (41.11%), road traffic (23.91%), blunt trauma (20.82%), penetrating knife injuries (5.85%), and firearm injuries (2.26%). Most TBI were classified as mild; 99.69% (Glasgow Coma Scale=15). Emergency room mortality was low (1.11%). The modified Kampala Trauma Score median was 8 (interquartile range 7-8). Conclusion: Mild TBI accounts for a significant percentage of all injuries presenting to a high-volume referral center in Honduras in 2013. Despite the high incidence of violence in this country, most TBI were accidental, secondary to road traffic accidents and falls. There is required further research with more recent data as well as with prospective data collection methods.